Fiber-doped modified electrolyte diaphragm for thermal battery, preparation method of fiber-doped modified electrolyte diaphragm and thermal battery prepared from fiber-doped modified electrolyte diaphragm
Through the preparation method of ceramic fiber-doped modified electrolyte separator, the problem of high internal resistance of thermal battery separator and short service life in extreme mechanical environments is solved, and the effect of reducing internal resistance, improving pulse resistance and extending service life is achieved.
Patent Information
- Application Number
- CN202411652932.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-04
AI Technical Summary
The internal resistance of existing thermal battery separators is large, which is difficult to meet the electrical performance requirements of high voltage and high power. At the same time, the service life is short in extreme mechanical environments, and traditional adsorbent materials are difficult to meet the needs of long-term work.
The preparation method of ceramic fiber doped modified electrolyte separator is adopted. The finished electrolyte separator is prepared by adding ceramic fibers to the porous active adsorbent material, mixing through a three-dimensional motion mixer, heating at high temperature, stirring evenly with eutectic salt and heat treatment, and finally pulverizing and tableting to prepare the finished electrolyte separator.
It reduces the internal resistance of the thermal battery separator, significantly improves the battery's pulse resistance, is suitable for high-power and large-pulse thermal batteries, and extends the service life of the thermal battery in extreme mechanical environments.
Smart Images

Figure CN119560575A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal batteries, and in particular relates to a fiber-doped modified electrolyte diaphragm for a thermal battery, a preparation method thereof, and a thermal battery prepared therefrom. Background Art
[0002] A thermal battery is a heat-activated primary reserve power source that uses a high-temperature molten salt as the electrolyte, which has its own heat source to melt and conduct electricity. It has the characteristics of short activation time, wide operating temperature, high energy density, and easy maintenance. Because the electrolyte of a thermal battery is a non-conductive solid at room temperature and has a storage life of more than ten years, it is widely used in weapons and equipment in military fields such as missiles, torpedoes, and smart ammunition.
[0003] At present, with the continuous use and development of thermal batteries, their service environment is becoming more and more harsh, and the requirements for the service performance of thermal batteries are becoming higher and higher. On the one hand, the internal resistance of traditional adsorbents is relatively large, and it is difficult to meet the ever-evolving electrical performance requirements such as high voltage and high power; on the other hand, the military field has increasingly stringent requirements for environmental resistance and mechanical properties. The service life of thermal battery products in extreme mechanical environments is relatively short, and traditional adsorbent materials are difficult to meet the long-term working requirements of thermal batteries in extreme mechanical environments.
[0004] CN202410086153.6 A lightweight flexible fiber composite diaphragm for thermal battery and its preparation method discloses a lightweight flexible fiber composite diaphragm, which improves the flexibility and specific surface area of the thermal battery diaphragm and improves the comprehensive performance of the thermal battery. The preparation method is complicated to operate, and the electrical performance effects such as internal resistance and service life are limited. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a fiber-doped modified electrolyte membrane for a thermal battery, a preparation method thereof, and a thermal battery prepared thereby. Compared with the prior art, the internal resistance of the thermal battery membrane is reduced, the pulse resistance of the battery is significantly improved, and the sheet strength of the electrolyte membrane is enhanced, thereby effectively improving the service life of the thermal battery product in extreme mechanical environments.
[0006] To achieve the above object, the present invention provides a method for preparing a fiber-doped modified electrolyte separator for a thermal battery, comprising the following steps:
[0007] (1) adding ceramic fibers to a porous active adsorbent material, mixing them evenly using a three-dimensional motion mixer and heating them at high temperature to obtain a mixed adsorbent material;
[0008] (2) further mixing the obtained mixed adsorbent material and eutectic salt and heat treating them, and crushing them through an 80-mesh sieve to obtain a finished electrolyte powder;
[0009] (3) The electrolyte powder is pressed into tablets to obtain a fiber-doped modified electrolyte membrane.
[0010] The ceramic fiber is a lightweight fibrous material with a fiber length of 5 to 30 μm and a fiber diameter of 0.1 to 1 μm. The ceramic fiber does not react with typical thermal battery electrolyte molten salts, including alumina ceramic fiber, aluminum carbonate fiber, aluminum silicate fiber, zirconium oxide ceramic fiber, and boron nitride fiber.
[0011] The porous active adsorbent material is a high-activity specific surface area structural adsorbent material, including a spherical porous structure or a lamellar stacking structure, and adopts one of active magnesium oxide, aluminum oxide, zirconium oxide, and silicon oxide.
[0012] The pressing pressure of the fiber-doped modified electrolyte membrane in step (3) is 2 t / cm 2 -6t / cm 2 .
[0013] In step (1), the powder composed of the porous active adsorbent material and the ceramic fiber is mixed in a three-dimensional motion mixer for not less than 4 hours to prepare a mixed powder with uniform composition; in step (2), the mixed adsorbent material and the eutectic salt are mixed for not less than 1 hour.
[0014] The eutectic salt is one of LiCl-KCl, LiF-LiCl-LiBr, LiF-LiBr-KBr, and LiCl-LiBr-KBr.
[0015] The firing temperature of the mixed adsorbent material is 200-800°C, and the firing time is not less than 4 hours; the firing temperature of the electrolyte powder is not less than 400-800°C, and the firing time is not less than 3 hours.
[0016] According to mass percentage, ceramic fiber: 2%-15%, porous active adsorbent material: 30%-60%, eutectic salt: 25-68%.
[0017] The fiber-doped modified electrolyte separator for thermal batteries prepared by the above preparation method.
[0018] A thermal battery, which adopts the above-mentioned preparation method to prepare a fiber-doped modified electrolyte diaphragm for a thermal battery or the above-mentioned fiber-doped modified electrolyte diaphragm for a thermal battery.
[0019] The beneficial effect of the present invention is that, compared with the prior art, the present invention effectively improves the molten salt path in the thermal battery diaphragm, reduces the internal resistance of the thermal battery, and significantly improves the battery's anti-pulse performance, making it suitable for use in high-power and large-pulse thermal batteries. In addition, fiber doping enhances the sheet quality of the thermal battery diaphragm, effectively improving the service life of thermal battery products in extreme mechanical environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the SEM microscopic morphology of the finished electrolyte powder of the present invention;
[0021] Figure 2 This is a macroscopic photograph of the electrolyte membrane drop test of Example 1 of the present invention;
[0022] Figure 3 This is a macroscopic photograph of the electrolyte diaphragm drop test of Comparative Example 1 of the present invention;
[0023] Figure 4 It is the discharge internal resistance curve of the fiber-doped modified electrolyte diaphragm thermal battery mechanical test of the present invention. DETAILED DESCRIPTION
[0024] The embodiments of the present invention are described below in conjunction with the accompanying drawings. In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings, in which preferred embodiments of the present invention are shown. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0025] A method for preparing a fiber-doped modified electrolyte separator for a thermal battery of the present invention comprises the following steps:
[0026] (1) adding ceramic fibers to a porous active adsorbent material, mixing them evenly using a three-dimensional motion mixer and heating them at high temperature to obtain a mixed adsorbent material;
[0027] (2) further mixing the obtained mixed adsorbent material and eutectic salt and heat treating them, and crushing them through an 80-mesh sieve to obtain a finished electrolyte powder;
[0028] (3) The electrolyte powder is pressed into tablets to obtain a fiber-doped modified electrolyte membrane.
[0029] The ceramic fiber is a lightweight fibrous material with a fiber length of 5 to 30 μm and a fiber diameter of 0.1 to 1 μm. The ceramic fiber does not react with typical thermal battery electrolyte molten salts, including alumina ceramic fiber, aluminum carbonate fiber, aluminum silicate fiber, zirconium oxide ceramic fiber, and boron nitride fiber.
[0030] The porous active adsorbent material is a high-activity specific surface area structural adsorbent material, including a spherical porous structure or a lamellar stacking structure, and adopts one of active magnesium oxide, aluminum oxide, zirconium oxide, and silicon oxide.
[0031] The pressing pressure of the fiber-doped modified electrolyte membrane in step (3) is 2 t / cm 2 -6t / cm2 .
[0032] In step (1), the powder composed of the porous active adsorbent material and the ceramic fiber is mixed in a three-dimensional motion mixer for not less than 4 hours to prepare a mixed powder with uniform composition; in step (2), the mixed adsorbent material and the eutectic salt are mixed for not less than 1 hour.
[0033] The eutectic salt is one of LiCl-KCl, LiF-LiCl-LiBr, LiF-LiBr-KBr, and LiCl-LiBr-KBr.
[0034] The firing temperature of the mixed adsorbent material is 200-800°C, and the firing time is not less than 4 hours; the firing temperature of the electrolyte powder is not less than 400-800°C, and the firing time is not less than 3 hours.
[0035] According to mass percentage, ceramic fiber: 2%-15%, porous active adsorbent material: 30%-60%, eutectic salt: 25-68%.
[0036] The fiber-doped modified electrolyte separator for thermal batteries prepared by the above preparation method.
[0037] A thermal battery, which adopts the above-mentioned preparation method to prepare a fiber-doped modified electrolyte diaphragm for a thermal battery or the above-mentioned fiber-doped modified electrolyte diaphragm for a thermal battery.
[0038] The present invention effectively improves the molten salt path in the thermal battery diaphragm, reduces the internal resistance of the thermal battery, and significantly improves the battery's anti-pulse performance, making it suitable for use in high-power and large-pulse thermal batteries. In addition, fiber doping enhances the sheet quality of the thermal battery diaphragm, effectively improving the service life of thermal battery products in extreme mechanical environments.
[0039] In a specific embodiment, the fiber-doped modified electrolyte membrane for thermal batteries of the present invention includes a porous active adsorbent material, ceramic fiber and eutectic salt. The adsorbent material and the eutectic salt are evenly mixed by a three-dimensional motion mixer and then treated at high temperature to prepare an electrolyte membrane sheet. Figure 1 This is the SEM microscopic morphology of the fiber-doped modified electrolyte diaphragm for the thermal battery of the present invention. Ceramic fibers are randomly distributed in the diaphragm, which enhances the molten salt passage of the electrolyte and plays a role in whisker toughening.
[0040] Compared with the ceramic diaphragm in the prior art, the fiber-doped modified electrolyte diaphragm for thermal batteries of the present invention has significantly enhanced powder tableting quality and has better electrical properties and environmental resistance mechanical properties.
[0041] Furthermore, in a preferred embodiment, the fiber-doped modified electrolyte membrane for thermal batteries comprises lightweight fibrous zirconia fibers, a porous active magnesium oxide adsorbent and a LiCl-KCl binary eutectic salt, and comprises the following components in mass percentage: lightweight fibrous zirconia fibers: 5%; porous active magnesium oxide adsorbent: 45%; LiCl-KCl binary eutectic salt: 50%.
[0042] When the above-mentioned specific ceramic fiber material components are used, the doping modification effect is the best, the electrolyte membrane has the best molding quality and electrical properties, and the prepared thermal battery has higher reliability.
[0043] The present invention provides a thermal battery, which is a fiber-doped modified electrolyte diaphragm for a thermal battery prepared by the above-mentioned preparation method.
[0044] The present invention is further described below through examples and comparative examples. In the following examples and comparative examples, preferably, the mass percentage of LiCl-KCl binary eutectic salt is 50%, the mass percentage of adsorbent is 50%, the mixing time of mixed adsorbent material and eutectic salt is 4 hours, the firing temperature of adsorbent material is 600℃, the firing time is 6h; the firing temperature of electrolyte powder is 700℃, the firing time is 4h. The final powder pressing pressure is 5T / cm 2 . Figure 1 The SEM microscopic morphology of the finished electrolyte powder of the present invention.
[0045] Example 1
[0046] A certain electrolyte diaphragm is modified by doping with zirconium oxide fiber. The weight of a single diaphragm is 18g and the diameter is 52mm. Three diaphragm pieces were dropped from a height of 50 cm in turn. The macroscopic photos after the test are as follows: Figure 2 As shown in the figure, after the drop test of the zirconia fiber-doped modified electrolyte separator, the electrolyte sheet remained basically intact, with a slight edge loss in some parts.
[0047] Comparative Example 1
[0048] A certain electrolyte diaphragm uses porous active magnesium oxide as the adsorbent material. The weight of a single diaphragm is 18g and the diameter is 52mm. Three diaphragm pieces were dropped from a height of 50cm in turn. The macroscopic photos after the test are as follows: Figure 3 As shown in the figure, the porous active magnesium oxide electrolyte membrane fails after the drop test, and the membrane is completely broken.
[0049] Example 2
[0050] A thermal battery adopts the fiber-doped modified electrolyte diaphragm for thermal batteries of the present invention, and performs a vibration electrical performance test after activation at 70°C for 4 hours. The internal resistance curve is as follows: Figure 4As shown, the internal resistance is between 0.052Ω and 0.056Ω after the hot battery is activated.
[0051] Comparative Example 2
[0052] A comparative example of the fiber-doped modified electrolyte separator for thermal battery of the present invention.
[0053] A thermal battery uses a porous active magnesium oxide adsorbent diaphragm. After being kept at 70°C for 4 hours, the vibration electrical performance test is performed after activation. The internal resistance curve is as follows: Figure 4 As shown: after the hot battery is activated, the internal resistance is between 0.056Ω and 0.062Ω.
[0054] from Figure 4 From the comparison of the two curves of the fiber-doped modified electrolyte membrane for thermal batteries and the porous active magnesium oxide adsorbent membrane, it can be seen that the thermal batteries modified by fiber doping in Example 2 of the present invention and Comparative Example 2 have been subjected to discharge performance tests. The fiber-doped modified electrolyte membrane for thermal batteries proposed in the present invention has smaller internal resistance within 180s after the thermal battery is activated, and the battery's anti-pulse performance is significantly improved, which is suitable for application in high-power and large-pulse thermal batteries.
[0055] Example 3
[0056] A certain thermal battery adopts the fiber-doped modified electrolyte diaphragm for thermal batteries of the present invention, and performs a vibration electrical performance test after activation after being kept at a constant temperature of 70°C for 4 hours. Its discharge performance data is shown in Table 1: the longitudinal vibration discharge time of the thermal battery prepared by the fiber-doped modified electrolyte diaphragm for thermal batteries is 1055.6s, and the transverse vibration discharge time is 1054.0s.
[0057] Comparative Example 3
[0058] A comparative example of the fiber-doped modified electrolyte separator for thermal battery of the present invention.
[0059] A certain thermal battery uses a porous active magnesium oxide adsorbent diaphragm. After being kept at a constant temperature of 70°C for 4 hours, the vibration electrical performance test was carried out after activation. The discharge performance data are shown in Table 1: the longitudinal vibration discharge time of the thermal battery prepared with the porous active magnesium oxide adsorbent diaphragm is 950.9s, and the transverse vibration discharge time is 832.8s.
[0060] Table 1
[0061]
[0062]
[0063] From the comparison of discharge data of fiber-doped modified electrolyte membrane for thermal battery and porous active magnesium oxide adsorbent membrane in Table 1, it can be seen that the thermal batteries modified by fiber doping in Example 3 of the present invention and Comparative Example 3 have been subjected to discharge performance tests. The fiber-doped modified electrolyte membrane for thermal battery proposed in the present invention has a longer working time in both the lateral vibration test and the longitudinal vibration test of the thermal battery than Comparative Example 3. Fiber doping enhances the sheet quality of the thermal battery membrane and effectively improves the service life of the thermal battery product in extreme mechanical environments.
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a fiber-doped modified electrolyte separator for a thermal battery, characterized in that: The steps include: (1) adding ceramic fibers to a porous active adsorbent material, mixing them evenly using a three-dimensional motion mixer and heating them at high temperature to obtain a mixed adsorbent material; (2) further mixing the obtained mixed adsorbent material and eutectic salt and heat treating them, and crushing them through an 80-mesh sieve to obtain a finished electrolyte powder; (3) The electrolyte powder is pressed into tablets to obtain a fiber-doped modified electrolyte membrane.
2. The method for preparing the fiber-doped modified electrolyte separator for thermal battery according to claim 1, characterized in that: The ceramic fiber is a lightweight fibrous material with a fiber length of 5 to 30 μm and a fiber diameter of 0.1 to 1 μm. The ceramic fiber does not react with typical thermal battery electrolyte molten salts, including alumina ceramic fiber, aluminum carbonate fiber, aluminum silicate fiber, zirconium oxide ceramic fiber, and boron nitride fiber.
3. The method for preparing the fiber-doped modified electrolyte separator for thermal battery according to claim 1, characterized in that: The porous active adsorbent material is a high-activity specific surface area structural adsorbent material, including a spherical porous structure or a lamellar stacking structure, and adopts one of active magnesium oxide, aluminum oxide, zirconium oxide, and silicon oxide.
4. The method for preparing the fiber-doped modified electrolyte separator for thermal battery according to claim 1, characterized in that: The pressing pressure of the fiber-doped modified electrolyte membrane in step (3) is 2 t / cm 2 -6t / cm 2 .
5. The method for preparing the fiber-doped modified electrolyte separator for thermal battery according to claim 1, characterized in that: In step (1), the powder composed of the porous active adsorbent material and the ceramic fiber is mixed in a three-dimensional motion mixer for not less than 4 hours to prepare a mixed powder with uniform composition; in step (2), the mixed adsorbent material and the eutectic salt are mixed for not less than 1 hour.
6. The method for preparing the fiber-doped modified electrolyte separator for thermal battery according to claim 1, characterized in that: The eutectic salt is one of LiCl-KCl, LiF-LiCl-LiBr, LiF-LiBr-KBr, and LiCl-LiBr-KBr.
7. The method for preparing the fiber-doped modified electrolyte separator for thermal battery according to claim 1, characterized in that: The firing temperature of the mixed adsorbent material is 200-800°C, and the firing time is not less than 4 hours; the firing temperature of the electrolyte powder is not less than 400-800°C, and the firing time is not less than 3 hours.
8. The method for preparing a fiber-doped modified electrolyte separator for a thermal battery according to any one of claims 1 to 7, characterized in that: According to mass percentage, ceramic fiber: 2%-15%, porous active adsorbent material: 30%-60%, eutectic salt: 25-68%.
9. A fiber-doped modified electrolyte separator for a thermal battery prepared by the preparation method according to any one of claims 1 to 8.
10. A thermal battery, characterized in that: The fiber-doped modified electrolyte diaphragm for thermal batteries or the fiber-doped modified electrolyte diaphragm for thermal batteries according to claim 9 is prepared by the preparation method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Lightweight flexible fiber composite diaphragm for thermal battery and preparation method of lightweight flexible fiber composite diaphragm
CN117913461A